Highway maintenanance management : case study at Projek Lebuhraya Utara Selatan (PLUS) - Harun, Mohd. Harzazi (2009)
The application of highway maintenance management is important. It is a centrally implemented tool for consistent decision making to optimize maintenance strategies for entire infrastructure network, in compliance with established policies. However, only some of the highway’s concessionaire has implement it. It may due to lack of awareness and lack of requirement by authority. The aim of this study is to investigate the highway maintenance management practiced by PLUS Expressway as the biggest highway concessionaire in Malaysia. Three objectives has been set for this study. The objectives are to study the current practice of the highway maintenance management at PLUS Expressway, to identify types of typical defects occurred to the highway assets and to identify the critical factors in selecting appropriate repair method for different type of defects. The methodology of this study were through document study, site visit and interview with related representative of the PLUS (concessionaire), OPUS-NMM (asset management consultant) and PROPEL (contractor). From this case study, it can be concluded that PLUS has appointed OPUS International (M) Bhd through its project team known as OPUS-Network Maintenance Management (NMM) as their asset management consultatnt. OPUS-NMM integrates network planning and management, periodic inspections, routine and planned maintenance to optimise the ‘whole of life’ cost of asset ownership. The defects that always occur are cracks and broken drain that may contribute to slope failure. Besides, the results show that the design and selecting method for the remedial works depends on the slope characteristic and the severity of the damage.